Mental health effects associated with COVID-19 financial assistance in South Korea: a comparison of employment status - Yoonjoo Choi; Eun-Joo Park; Soon-Young Lee; Hee-Yeon Kim; Weon-Young Lee (BMC, 2024)
Abstract Background COVID-19 has created tensions across different sectors of the society, but the impact has been unequal. Vulnerable people have been most affected, especially those with insecure employment and who have experienced economic hardships due to unemployment and lost wages. The combination of social change and economic hardships due to the pandemic increases the risk of poor mental health. Some countries have utilized financial assistance to alleviate economic hardships caused by COVID-19, and in South Korea, the central and local governments have implemented COVID-19 financial assistance. This study analysed the impact of financial assistance on mental health associated with working status during the COVID-19 pandemic in South Korea. Methods The participants of this study were randomly selected from residents of Gyeonggi-do after being proportionally allocated by resident registration population status. A total of 1,000 adult males and females aged 19 years or older in Gyeonggi-do who received financial assistance from the central and local governments were selected. A retrospective pre-post-study design was applied, and mental health surveys including the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-item scale (GAD-7) were applied. Results The results show that depression scores averaged 5.5 and anxiety scores averaged 4.4 before COVID-19 Financial Assistance. It is similar to the national average of 5.1 and 4.5 respectively at that time. After the assistance, depression scores dropped to 4.5, and anxiety scores dropped to 3.2. Before the assistance, depression and anxiety were higher among temporary day labourers with less job security, and they showed the most significant improvement in mental health. For full-time workers, there was no significant change in anxiety or depression after receiving the assistance. Conclusions Financial assistance can provide material resources and also positively affect mental health. In particular, it had a greater impact on the relatively vulnerable groups, such as those in unstable employment.